Polymer for ArF photoresist, preparation method of polymer and photoresist composition

By designing a polymer containing lactone, furan structure and flexible monomer, the problem of poor adhesion and pattern stability of ArF photoresist when improving etch resistance and contrast is solved, and the balance of high adhesion, etch resistance and pattern stability is achieved.

CN119708332APending Publication Date: 2025-03-28VALIANT CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411963988.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

While improving etch resistance and contrast, existing ArF photoresist leads to reduced adhesion and poor stability of graphics lines, making it difficult to take into account high adhesion, etch resistance and graphics stability.

Method used

A polymer was designed with a structure containing 2-methacrylic acid-2-[(hexahydro-5-oxo-2,6-methylfurano[3,2-b]furan-3-yl)oxy]-2-oxyethyl ester monomer. By introducing lactone, furan structure and flexible monomer, the polarity and hydrophilicity of the polymer are enhanced, and stability and flexibility are improved through the adamantane structure.

Benefits of technology

The adhesion, etch resistance and pattern lines of photoresist are significantly improved, ensuring the application performance of photoresist in high resolution and small-size chip manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708332A_ABST
    Figure CN119708332A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of photoresists, in particular to a polymer for an ArF photoresist and a preparation method thereof and a photoresist composition, the structural general formula of the polymer is as follows: # imgabs0 # x, y, z and m are mass fractions of polymer repetitive units respectively, x is selected from 5-10%, y is selected from 10-20%, z is selected from 25-50%, m is selected from 35-50%, the weight-average molecular weight of the polymer is selected from 2000-20000 Da, m is selected from 5-20%, and m is selected from 5-20%. The molecular weight dispersion coefficient of the polymer is 1.0 to 3.0. The preparation method comprises the following steps: mixing a monomer A, a monomer B, a monomer C, a monomer D and a free radical initiator, dissolving the mixture in an electronic-grade reaction solvent to prepare a mixed solution, preparing a polymer by controlling the reaction temperature and the reaction time, and after the reaction is finished, dropwise adding the reaction system into a poor solvent for granulation to obtain the polymer. The photoresist composition prepared from the polymer is high in adhesive force, good in corrosion resistance and stable in pattern.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polymer used for ArF photoresist and a preparation method thereof and a photoresist composition, belonging to the technical field of photoresists. Background Art

[0002] As the integration of integrated circuits continues to increase, the size of devices is required to be smaller and smaller, and the resolution of photoresists is developing from micron and submicron to nanometer level. ArF exposure is divided into dry lithography and immersion lithography. Combined with multiple exposure technology, the resolution covers 90~7nm and is the mainstream process for chip manufacturing.

[0003] As semiconductor process nodes continue to develop towards higher density and smaller size, the performance requirements of ArF lithography technology and corresponding photoresists are also constantly increasing. In particular, there are many challenges in terms of photoresist resolution, adhesion, etching resistance, post-imaging defect control, line width uniformity, etc.

[0004] At present, (meth) acrylic polymer is one of the main materials of ArF photoresist, which has good light transmittance at 193nm. In order to meet the etching resistance of photoresist and improve contrast, a large number of aliphatic ring structures are introduced into the photoresist polymer, but this will lead to a decrease in the adhesion between the photoresist and the substrate. Introducing maleic anhydride monomer into the photoresist polymer enhances the polarity of the polymer and its hydrophilicity to improve adhesion, but the resulting mold is relatively brittle and the stability of the graphic lines after development is poor.

[0005] In order to overcome the above defects and improve the performance of the photoresist composition, it is necessary to design a polymer for ArF photoresist that has high adhesion, good etching resistance and stable pattern. Summary of the invention

[0006] The present invention aims at the deficiencies of the prior art and provides a polymer for ArF photoresist and a preparation method thereof and a photoresist composition. The photoresist composition prepared by the polymer has high adhesion, good etching resistance and good pattern line stability.

[0007] The technical solution of the present invention to solve the above technical problem is as follows: a polymer for ArF photoresist, the general structural formula of the polymer is as follows:

[0008]

[0009]

[0010] x, y, z, and m are respectively the mass fractions of the polymer repeating units, x is selected from 5-10%, y is selected from 10-20%, z is selected from 25-50%, and m is selected from 35-50%. The weight average molecular weight of the polymer is selected from 2000-20000Da, and the molecular weight dispersion coefficient of the polymer is selected from 1.0-3.0.

[0011] On the basis of the above technical solution, the present invention can also be improved as follows:

[0012] Preferably, in the repeating unit of the polymer, x is selected from 5-10%, y is selected from 10-15%, z is selected from 30-50%, and m is selected from 35-45%.

[0013] Preferably, the weight average molecular weight of the polymer is selected from 6000-10000 Da, and the molecular weight dispersion coefficient of the polymer is selected from 1.0-1.8.

[0014] The present invention also discloses a method for preparing a polymer for ArF photoresist, which is characterized in that the preparation method comprises the following steps: mixing monomer A, monomer B, monomer C, monomer D and a free radical initiator and dissolving them in an electronic grade reaction solvent to prepare a mixed solution, preparing a polymer by controlling the reaction temperature and reaction time, and after the reaction is completed, dripping the reaction system into a poor solvent to granulate the polymer.

[0015] The monomer A is 2-methyl-2-adamantyl methacrylate, the monomer B is 3,5-dihydroxy-1-adamantyl methacrylate, the monomer C is 2-methacrylate-2-[(hexahydro-5-oxo-2,6-methylfurano[3,2-b]furan-3-yl)oxy]-2-oxoethyl ester, and the monomer D is 2-isopropyl-2-adamantyl methacrylate.

[0016] Furthermore, the monomer A accounts for 5-10% of the total mass of the monomers, the monomer B accounts for 10-20% of the total mass of the monomers, the monomer C accounts for 25-50% of the total mass of the monomers, and the monomer D accounts for 35-50% of the total mass of the monomers.

[0017] Preferably, the monomer A accounts for 5-10% of the total mass of the monomers, the monomer B accounts for 10-15% of the total mass of the monomers, the monomer C accounts for 30-50% of the total mass of the monomers, and the monomer D accounts for 35-45% of the total mass of the monomers.

[0018] Further, the free radical initiator is selected from any one of azobisisobutyronitrile, benzoyl peroxide, azobisisovaleronitrile and dimethyl azobisisobutyrate. The amount of the free radical initiator is 1-20% of the total mass of the monomers (the sum of the mass of monomer A, monomer B and monomer C).

[0019] Preferably, the free radical initiator is azobisisobutyronitrile.

[0020] Preferably, the amount of the free radical initiator is 5-10% of the total weight of the monomers.

[0021] Furthermore, the electronic grade reaction solvent is selected from any one of propylene glycol methyl ether, propylene glycol methyl ether acetate, methyl isobutyl carbinol, and dipropylene glycol methyl ether.

[0022] Preferably, the electronic grade reaction solvent is propylene glycol methyl ether.

[0023] Furthermore, the reaction temperature is 40-100° C., and the reaction time is 2-10 hours.

[0024] Preferably, the reaction temperature is 70-90° C., and the reaction time is 2-5 hours.

[0025] Furthermore, the poor solvent is selected from at least one of methanol, ethanol and water.

[0026] The invention discloses a photoresist composition, which comprises a polymer of the ArF photoresist, a photoacid generator and an electronic grade solvent, wherein the polymer is the polymer of the ArF photoresist of the invention.

[0027] The beneficial effects of the present invention are:

[0028] (1) The polymer structure of the present invention contains 2-methylacrylate-2-[(hexahydro-5-oxo-2,6-methylfurano[3,2-b]furan-3-yl)oxy]-2-oxyethyl ester monomer, which also contains lactone and furan structures, thereby enhancing the polarity of the polymer and greatly improving the adhesion between the photoresist and the substrate; and at the same time, because the polarity of the monomer structure is relatively strong, the interaction between the polymer and the solvent is also increased, and the pattern lines after development are more stable and clearer.

[0029] (2) The polymer structure of the present invention has two acid-labile hydroxyl groups, which enhances the hydrophilicity of the polymer and improves the adhesion.

[0030] (3) The polymer structure of the present invention contains a large amount of adamantane structure, which is a stable cyclic aliphatic structure, and introduces a flexible monomer methacrylate-2-isopropyl-2-adamantyl ester, which greatly enhances the stability and flexibility of the photoresist composition, greatly improves the corrosion resistance of the composition, improves the contrast of the photoresist, and has a higher resolution after imaging.

[0031] (4) The preparation method of the polymer of the present invention is simple and convenient. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1For polymer Polymer C 13 C-NMR spectrum;

[0033] Figure 2 This is a cross-sectional morphology scan image of composition 3;

[0034] Figure 3 This is a scanned image of the cross-sectional morphology of composite 8. DETAILED DESCRIPTION

[0035] The specific implementation of the present invention is described in detail below. The present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed.

[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and are not intended to limit the present invention.

[0037] 1. Polymer Preparation Example

[0038] Example 1

[0039] 1.6 g of monomer A (2-methyl-2-adamantyl methacrylate), 2.4 g of monomer B (3,5-dihydroxy-1-adamantyl methacrylate), 6.0 g of monomer C (2-methacrylate-2-[(hexahydro-5-oxo-2,6-methylfurano[3,2-b]furan-3-yl)oxy]-2-oxoethyl ester), 10.0 g of monomer D (2-isopropyl-2-adamantyl methacrylate) and 2.0 g of azobisisobutyronitrile were dissolved in 180.0 g of electronic grade dipropylene glycol methyl ether to prepare a mixed solution, the reaction temperature was raised to 60-70° C., the reaction was kept warm for 8 hours, and after the reaction was completed, the system was cooled to room temperature and slowly added dropwise to 1000.0 g of methanol to precipitate a white solid, which was filtered and dried to obtain 13.0 g of polymer Polymer A with a yield of 65%, Mw=7219 Da, and PDI=1.63 (preparation of polymer Polymer A). A, the mass ratio of monomer A, monomer B, monomer C and monomer D is 8:12:30:50).

[0040] Example 2

[0041] 1.6 g of monomer A (2-methyl-2-adamantyl methacrylate), 2.4 g of monomer B (3,5-dihydroxy-1-adamantyl methacrylate), 6.0 g of monomer C (2-methacrylate-2-[(hexahydro-5-oxo-2,6-methylfurano[3,2-b]furan-3-yl)oxy]-2-oxoethyl ester), 10.0 g of monomer D (2-isopropyl-2-adamantyl methacrylate) and 1.5 g of azobisisobutyronitrile were dissolved in 180.0 g of electronic grade methyl isobutyl methanol to prepare a mixed solution, which was pumped into 80.0 g of electronic grade methyl isobutyl methanol by a metering pump, the reaction temperature was raised to 80-90° C., the reaction was kept warm for 4 hours, the system was cooled to room temperature after the reaction was completed, and the solution was slowly added dropwise to 1000.0 g of methanol to precipitate a white solid, which was filtered and dried to obtain a polymer Polymer B 13.4 g, yield 67%, Mw=8351 Da, PDI=1.71 (when preparing polymer Polymer B, the mass ratio of monomer A, monomer B, monomer C and monomer D is 8:12:30:50).

[0042] Example 3

[0043] 1.6 g of monomer A (2-methyl-2-adamantyl methacrylate), 2.4 g of monomer B (3,5-dihydroxy-1-adamantyl methacrylate), 7.0 g of monomer C (2-methacrylate-2-[(hexahydro-5-oxo-2,6-methylfurano[3,2-b]furan-3-yl)oxy]-2-oxoethyl ester), 9.0 g of monomer D (2-isopropyl-2-adamantyl methacrylate), and 1.5 g of azobisisovaleronitrile were dissolved in 200.0 g of electronic grade propylene glycol methyl ether to prepare a mixed solution, the reaction temperature was raised to 70-80° C., the reaction was kept warm for 10 hours, and after the reaction was completed, the system was cooled to room temperature and slowly added dropwise to 1000.0 g of water to precipitate a white solid, which was filtered and dried to obtain 11.0 g of polymer Polymer C with a yield of 55%, Mw=8738 Da, and PDI=1.70 (preparation of polymer Polymer C, the mass ratio of monomer A, monomer B, monomer C and monomer D is 8:12:35:45).

[0044] Nuclear magnetic resonance detection is: 13C-NMR (400MHz, (CD3)2CO), δ=20.396 (methyl carbon signal peak in 2-methyl-2-adamantyl methacrylate), δ=68.003 (carbon signal peak connected to hydroxyl group in 3,5-dihydroxy-1-adamantyl methacrylate), δ=167.894 (carbonyl carbon signal peak of lactone structure in 2-[(hexahydro-5-oxo-2,6-methylfuran[3,2-b]furan-3-yl)oxy]-2-oxoethyl 2-methacrylate), δ=18.106 (methyl carbon signal peak in 2-isopropyl-2-adamantyl methacrylate), as shown in the attached Figure 1 shown.

[0045] Example 4

[0046] 1.2 g of monomer A (2-methyl-2-adamantyl methacrylate), 2.4 g of monomer B (3,5-dihydroxy-1-adamantyl methacrylate), 8.0 g of monomer C (2-methacrylate-2-[(hexahydro-5-oxo-2,6-methylfurano[3,2-b]furan-3-yl)oxy]-2-oxoethyl ester), 8.4 g of monomer D (2-isopropyl-2-adamantyl methacrylate), and 1.5 g of dimethyl azobisisobutyrate were dissolved in 200.0 g of electronic grade propylene glycol methyl ether acetate to prepare a mixed solution, the reaction temperature was raised to 70-80° C., and the reaction was kept warm for 2 hours. After the reaction was completed, the system was cooled to room temperature and slowly added dropwise to 1000.0 g of ethanol to precipitate a white solid, which was filtered and dried to obtain 12.6 g of polymer Polymer D with a yield of 63%, Mw=8197 Da, and PDI=1.76 (preparation of polymer Polymer D, the mass ratio of monomer A, monomer B, monomer C and monomer D is 6:12:40:42).

[0047] Example 5

[0048] 1.6 g of monomer A (2-methyl-2-adamantyl methacrylate), 2.4 g of monomer B (3,5-dihydroxy-1-adamantyl methacrylate), 6.0 g of monomer C (2-methacrylate-2-[(hexahydro-5-oxo-2,6-methylfurano[3,2-b]furan-3-yl)oxy]-2-oxoethyl ester), 10.0 g of monomer D (2-isopropyl-2-adamantyl methacrylate), and 1.5 g of benzoyl peroxide were dissolved in 150.0 g of electronic grade propylene glycol methyl ether to prepare a mixed solution, the reaction temperature was raised to 50-60° C., the reaction was kept warm for 6 hours, and after the reaction was completed, the system was cooled to room temperature and slowly added dropwise to 1000.0 g of methanol to precipitate a white solid, which was filtered and dried to obtain 12.0 g of polymer Polymer E with a yield of 60%, Mw=11351 Da, and PDI=1.81 (preparation of polymer Polymer E E, the mass ratio of monomer A, monomer B, monomer C and monomer D is 8:12:30:50).

[0049] Example 6

[0050] 1.6 g of monomer A (2-methyl-2-adamantyl methacrylate), 2.4 g of monomer B (3,5-dihydroxy-1-adamantyl methacrylate), 6.0 g of monomer C (2-methacrylate-2-[(hexahydro-5-oxo-2,6-methylfurano[3,2-b]furan-3-yl)oxy]-2-oxoethyl ester), 10.0 g of monomer D (2-isopropyl-2-adamantyl methacrylate), and 3.0 g of azobisisobutyronitrile were dissolved in 150.0 g of electronic grade methyl isobutyl methanol to prepare a mixed solution, the reaction temperature was raised to 70-80° C., the reaction was kept warm for 6 hours, and after the reaction was completed, the system was cooled to room temperature and slowly added dropwise to 1000.0 g of ethanol to precipitate a white solid, which was filtered and dried to obtain 11.4 g of polymer Polymer F with a yield of 57%, Mw=4735 Da, and PDI=1.43 (preparation of polymer Polymer F, the mass ratio of monomer A, monomer B, monomer C and monomer D is 8:12:30:50).

[0051] Example 7

[0052] 1.6 g of monomer A (2-methyl-2-adamantyl methacrylate), 2.4 g of monomer B (3,5-dihydroxy-1-adamantyl methacrylate), 6.0 g of monomer C (2-methacrylate-2-[(hexahydro-5-oxo-2,6-methylfurano[3,2-b]furan-3-yl)oxy]-2-oxoethyl ester), 10.0 g of monomer D (2-isopropyl-2-adamantyl methacrylate), and 0.5 g of azobisisovaleronitrile were dissolved in 150.0 g of electronic grade propylene glycol methyl ether acetate to prepare a mixed solution, the reaction temperature was raised to 90-100° C., the reaction was kept warm for 3 hours, and after the reaction was completed, the system was cooled to room temperature and slowly added dropwise to 1000.0 g of methanol to precipitate a white solid, which was filtered and dried to obtain 10.0 g of polymer Polymer G with a yield of 50%, Mw=14938 Da, and PDI=1.95 (preparation of polymer Polymer G, the mass ratio of monomer A, monomer B, monomer C and monomer D is 8:12:30:50).

[0053] 2. Preparation of Photoresist Composition

[0054] The polymer prepared in the above embodiment is mixed with a photoacid generator (4-tert-butylphenyl diphenylsulfonium nonafluorobutane sulfonate) and an electronic grade solvent propylene glycol methyl ether to prepare a photoresist composition with a certain solid content. The formula of the photoresist composition is shown in Table 1:

[0055] Table 1 Photoresist composition formula

[0056]

[0057] The structural formula of polymer Polymer X is as follows:

[0058]

[0059] 3. Photoresist composition performance test

[0060] The photoresist composition was spin-coated on a 6-inch silicon wafer at a speed of 0rpm / 10s, 200rpm / 2s, 0rpm / 2s, and 1500rpm / 30s. After the spin coating was completed, it was baked on a hot plate at 90°C for 1 minute and then placed on a cold plate for cooling. 2 Under the exposure energy dose, a photolithography pattern was obtained, and the adhesion performance was tested and the image was scanned; the photoresist continued to be etched by oxygen reactive ion etching to test the etching resistance. The specific results are shown in Table 2. The test methods involved are as follows:

[0061] Adhesion performance: observe the photoresist pattern of the test sample for inversion or peeling;

[0062] Etching resistance: Calculate the relative etching rate of the sample.

[0063] Table 2 Photoresist composition performance test results

[0064]

[0065] As can be seen from Table 2, after the use of the photoresist polymer of the present invention (composition 1 to composition 7), since the polymer contains 3,5-dihydroxy-1-adamantyl methacrylate and 2-methacrylate-2-[(hexahydro-5-oxo-2,6-methylfurano[3,2-b]furan-3-yl)oxy]-2-oxyethyl ester monomers, the hydroxyl, lactone and furan structures therein greatly enhance the polarity and hydrophilicity of the polymer, and improve the adhesion between the photoresist and the substrate (no collapse). However, the composition 8 prepared from the polymer X in the comparative example has a smaller polarity and insufficient adhesion of the photoresist (partial collapse).

[0066] From the relative values ​​of the etching rates, it can be seen that after the use of the photoresist polymers described in the present invention (compositions 1 to 7), since the polymers contain a large amount of adamantane aliphatic ring structures and the flexible monomer methacrylate-2-isopropyl-2-adamantyl ester is introduced, the stability and flexibility of the photoresist composition are greatly enhanced, thereby improving the etching resistance, and the etching rate is significantly lower than that of composition 8.

[0067] In summary, the photoresist polymer described in the present invention can significantly improve the adhesion and etching resistance of the photoresist composition.

[0068] Determination of photoresist cross-sectional morphology: Use scanning electron microscope to observe the cross-sectional morphology. The test results are shown in Figure 2-Figure 3 , Figure 2 This is a scanned image of composition 3. Figure 3 This is a scanned image of composition 8. Figure 2 and Figure 3 It can be seen from the comparison that after the use of the polymer of the present invention (composition 3), the morphology of the pattern is clear and the roughness is low (3.77), which significantly improves the resolution of the photoresist development pattern and the stability of the pattern, while the morphology of the pattern of composition 8 is rough and blurred and the roughness is large (11.94). In comparison, the polymer of the present invention has good application prospects in photoresists.

[0069] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0070] For those skilled in the art, several modifications and improvements may be made without departing from the concept of the present invention, all of which belong to the protection scope of the present invention. The protection scope of the present invention shall be based on the attached claims.

Claims

1. A polymer for ArF photoresist, characterized in that The general structural formula of the polymer is as follows: x, y, z, and m are respectively the mass fractions of the polymer repeating units, x is selected from 5-10%, y is selected from 10-20%, z is selected from 25-50%, and m is selected from 35-50%. The weight average molecular weight of the polymer is selected from 2000-20000Da, and the molecular weight dispersion coefficient of the polymer is selected from 1.0-3.

0.

2. A polymer for ArF photoresist according to claim 1, characterized in that: In the repeating unit of the polymer, x is selected from 5-10%, y is selected from 10-15%, z is selected from 30-50%, and m is selected from 35-45%.

3. A polymer for ArF photoresist according to claim 1, characterized in that: The weight average molecular weight of the polymer is selected from 6000-10000 Da, and the molecular weight dispersion coefficient of the polymer is selected from 1.0-1.

8.

4. A method for preparing a polymer for ArF photoresist according to any one of claims 1 to 3, characterized in that: The preparation method comprises: mixing monomer A, monomer B, monomer C, monomer D and a free radical initiator and dissolving them in an electronic grade reaction solvent to prepare a mixed solution, preparing a polymer by controlling the reaction temperature and reaction time, and after the reaction is completed, dripping the reaction system into a poor solvent to granulate and obtain the polymer; The monomer A is 2-methyl-2-adamantyl methacrylate, the monomer B is 3,5-dihydroxy-1-adamantyl methacrylate, the monomer C is 2-methacrylate-2-[(hexahydro-5-oxo-2,6-methylfurano[3,2-b]furan-3-yl)oxy]-2-oxoethyl ester, and the monomer D is 2-isopropyl-2-adamantyl methacrylate.

5. The method for preparing a polymer for ArF photoresist according to claim 4, characterized in that: The monomer A accounts for 5-10% of the total mass of the monomers, the monomer B accounts for 10-20% of the total mass of the monomers, the monomer C accounts for 25-50% of the total mass of the monomers, and the monomer D accounts for 35-50% of the total mass of the monomers.

6. The method for preparing a polymer for ArF photoresist according to claim 4, characterized in that: The free radical initiator is selected from any one of azobisisobutyronitrile, benzoyl peroxide, azobisisovaleronitrile and dimethyl azobisisobutyrate.

7. The method for preparing a polymer for ArF photoresist according to claim 4, characterized in that: The electronic grade reaction solvent is selected from any one of propylene glycol methyl ether, propylene glycol methyl ether acetate, methyl isobutyl carbinol, and dipropylene glycol methyl ether.

8. The method for preparing a polymer for ArF photoresist according to claim 4, characterized in that: The reaction temperature is 40-100° C., and the reaction time is 2-10 hours.

9. The method for preparing a polymer for ArF photoresist according to claim 4, characterized in that: The poor solvent is selected from at least one of methanol, ethanol and water.

10. A photoresist composition, characterized in that: The photoresist composition comprises the polymer of the ArF photoresist, a photoacid generator and an electronic grade solvent. The polymer is the polymer of the ArF photoresist according to any one of claims 1 to 3, or the polymer is the polymer prepared by the preparation method according to any one of claims 4 to 9.

Citation Information

Cited By

  • Polymer for ArF photoresist, preparation method and photoresist composition

    CN120965929A

  • A polymer for arf photoresist, a preparation method and a photoresist composition

    CN120965929B